1974
DOI: 10.1042/bj1420685
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase activity in cardiac muscle during embryonic and postnatal development

Abstract: Cytoplasmic thymidine kinase from cardiac muscle of the rat has been characterized.It has a pH optimum of 9.0 and a Km value for thymidine of 1.6/UM. The sedimentation coefficient ofthis enzyme in sucrose gradients is 4.5 S, which represents a molecular weight of approx. 69000. Thymidine kinase prepared from cardiac muscle of foetal, neonatal and adult rats is inhibited by dTTP and dTDP; there is neither inhibition nor stimulation by dTMP, dCTP, dATP, dGTP or cyclic AMP. The activity of thymidine kinase in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We have re-examined these issues (Limas & Limas, 1978) by separately determining the activity of three DNA polymerases (x, ,B and ;P) from muscle and non-muscle cells of the developing myocardium. Decline in muscle cell polymerases was much less (30 40 % compared with day 1) than previous studies (Doyle et al, 1974;Gillette & Claycomb, 1974;Claycomb, 1975;Hubscher et al, 1977;Claycomb, 1977) have indicated and occurred entirely within the first 2 weeks of post-natal life; non-muscle-cell polymerases were essentially unchanged when expressed as [3H]dTMP/106 cells. (b) DNA polymerase activities in quiescent cells cannot predict the ability of the cells to proliferate in response to stimuli.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…We have re-examined these issues (Limas & Limas, 1978) by separately determining the activity of three DNA polymerases (x, ,B and ;P) from muscle and non-muscle cells of the developing myocardium. Decline in muscle cell polymerases was much less (30 40 % compared with day 1) than previous studies (Doyle et al, 1974;Gillette & Claycomb, 1974;Claycomb, 1975;Hubscher et al, 1977;Claycomb, 1977) have indicated and occurred entirely within the first 2 weeks of post-natal life; non-muscle-cell polymerases were essentially unchanged when expressed as [3H]dTMP/106 cells. (b) DNA polymerase activities in quiescent cells cannot predict the ability of the cells to proliferate in response to stimuli.…”
mentioning
confidence: 63%
“…The implication (Claycomb, 1976), however, that this decline is responsible for the restriction in proliferative capacity of myocardial cells is complicated by two considerations. (a) None of the reported studies (Doyle et al, 1974;Gillette & Claycomb, 1974;Claycomb, 1975Claycomb, , 1976Hubscher et al, 1977;Claycomb, 1977) has taken into consideration that myocardial cell size increases considerably during early post-natal growth (Sasaki et al, 1968;Katzberg et al, 1977) and that expression of enzymic activity per mg of protein may grossly overestimate the magnitude of DNA polymerase decline. The cellular heterogeneity of the heart has also been ignored, despite the fact that non-muscle (interstitial and endothelial) cells retain their proliferative capacity to adulthood (Morkin & Ashford, 1968; Grove et al, 1969).…”
mentioning
confidence: 99%
“…DNA polymerase has been found to accurately reflect myocardial cell proliferative activity (6,9,10). Cardiac DNA polymerase activity not only has been characterized (5), but this enzyme as well as another myocardial replicative enzyme, thymidine kinase, have correlated with [3H]thymidine incorporation as an indicator of ventricular mitotic activity (5,14). Moreover, we have used autoradiography in this study to verify that DNA polymerase activity reflects cardiac muscle cell division in both the control and 6-OHDtreated rats.…”
Section: Discussionmentioning
confidence: 90%
“…DNA synthesis and hence cell proliferation in terminally differentiating cardiac muscle of the rat decrease progressively after birth and essentially cease by the middle of the third week of postnatal development (Claycomb, 1973(Claycomb, , 1975a. Temporally correlated with this loss in synthetic activity is an almost complete loss in activity of DNA polymerase a and thymidine kinase (Claycomb, 1973(Claycomb, , 1975aGillette & Claycomb, 1974>. The activity of DNA polymerase remains relatively constant during postnatal development (Claycomb, 1975a).…”
mentioning
confidence: 99%